Mentoring, gender and ideological perspectives: a case study - Özen, Rana. (Thesis (Ph.D.) - Bogazici University. Institute of Social Sciences, 1998., 1998)
The purpose of this study is to find out the differences of mentoring relationship in a different organizational setting than described in the literature. This organization is characterized by its strong values that are shared by its members who have ideological bonds among them. The organization operates in the education sector, and it is one of private preparatory institutions for central university examination. The sample for this study consists of a total 34 respondents (17 dyads) composed of 16 female and 18 male teachers. In-depth interviews with dyads are conducted in Turkish. Additional interviews are conducted with the General Manager, unit managers of the institution, 11 members of staff, and 50 students and 50 parents as customers of the institution. The results of this study indicated that different mentoring relationships and different mentor types may be defined in a different organizational setting. The research was also formed on the differences about mentoring, and related factors. Different concepts were defined, and some unexpected findings were found in the organization. There is a formal mentoring program and a study group system in the institution. "Performance" is important as well as "ideological similarity" in the relationship between mentors and proteges. "Dominance of men" and "sex segregation" are different properties of the institution. It is seen that, new concepts that are observed in this organization were related to the experience of mentoring relationship. The new concepts, such as "togetherness", "altruism", "self-sacrifice", "trying to be a pure-bred horse", "being wise leader", "trying to do good things", "to give alms for knowledge", "co-religionist perspective", "working for God's sake", "transferring moral and ethical values", "ideological fit" and "consultation climate" appears to bring new dimensions to mentoring relationships in the organization.
Keywords: Mentoring.; Mentoring in education.